2011
DOI: 10.1007/s12272-011-0413-8
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer potential of magnolol for lung cancer treatment

Abstract: Lung malignancy is a major cause of human mortality. As such, safe pharmacological agents that can detect lung cancer are urgently required. Magnolol has been reported to have anticancer property. However, it is still unclear whether magnolol induces apoptosis of lung carcinoma cells. In this study, magnolol inhibited cell growth, increased lactate dehydrogenase release, and modulated cell cycle in human lung carcinoma A549 cells. Magnolol induced the activation of caspase-3 and cleavage of Poly-(ADP)-ribose p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 36 publications
0
18
0
1
Order By: Relevance
“…Furthermore, it also increases the expression of the genes involved in malignant conversion and tumor promotion [8,63,106,107,108,109,110,111,112,113,114,115]. It is now well known that the primary targets of MAG are NF-κB and NF-κB regulated proteins and that MAG induces cell death and reduces cell proliferation by inhibition of NF-κB activity [116,117,118]. MAG prevents invasion and migration of cancer cells by reversal of epithelial-mesenchymal transition (EMT) via inhibition of NF-κB activation.…”
Section: Molecular Targets Of Magnololmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it also increases the expression of the genes involved in malignant conversion and tumor promotion [8,63,106,107,108,109,110,111,112,113,114,115]. It is now well known that the primary targets of MAG are NF-κB and NF-κB regulated proteins and that MAG induces cell death and reduces cell proliferation by inhibition of NF-κB activity [116,117,118]. MAG prevents invasion and migration of cancer cells by reversal of epithelial-mesenchymal transition (EMT) via inhibition of NF-κB activation.…”
Section: Molecular Targets Of Magnololmentioning
confidence: 99%
“…Seo J.U. et al, in 2011, revealed that MAG can alter the cell cycle in A549 cells and can also mediate caspase-dependent apoptosis via downregulation of NF-κB/Rel A in the nucleus [118]. Another study on small lung cancer H460 cells demonstrated that MAG initiates cell death via autophagy instead of apoptosis [120].…”
Section: Effect Of Magnolol In Different Cancersmentioning
confidence: 99%
“…17, 18 Magnolol induces apoptosis in the cells of many human cancers, including gallbladder cancer, non-small cell lung cancer, prostate cancer, human breast cancer, bladder cancer, colon cancer, and skin cancer. 9, 10, 11, 12, 14, 18, 19, 20, 21, 22, 23, 24 Therefore, magnolol has been suggested as a potential apoptosis-targeting drug. 25 Together, the results from the existing in vivo and in vitro studies have indicated that magnolol is a promising candidate for the development of new strategies for preventing and/or treating skin cancers in humans.…”
mentioning
confidence: 99%
“…[7] Cells were passaged after reaching confluence every 7-10 days, and passage numbers from 4 to 6 were used for experiments. [8]…”
Section: Methodsmentioning
confidence: 99%